2017
DOI: 10.1021/acs.jpcc.7b04310
|View full text |Cite
|
Sign up to set email alerts
|

Transient Translational and Rotational Water Defects in Gas Hydrates

Abstract: We report our observations of the transient formation of the translational and rotational defects in the host lattice of methane hydrates. We perform molecular dynamics simulations of a fully occupied methane hydrate system and find that the hydrogen bonds of a water molecule can be thermally broken, and the water molecule can then rotate more freely. We observe the formation of transient Bjerrum defects around the water molecule, and the two hydrogens of the water molecule can be interchanged when the transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…Previous works have demonstrated that in gas hydrate crystal structures, the arrangement of their hydrogen bond network is “ice-like” but with slight distortions. Further stabilized by encaging a guest molecule, the cage structures in gas hydrate crystals are considered relatively rigid and the lattice water molecules are largely restricted from rotation and translation . The rigidity of the gas hydrate structure may influence different steps of the reaction mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Previous works have demonstrated that in gas hydrate crystal structures, the arrangement of their hydrogen bond network is “ice-like” but with slight distortions. Further stabilized by encaging a guest molecule, the cage structures in gas hydrate crystals are considered relatively rigid and the lattice water molecules are largely restricted from rotation and translation . The rigidity of the gas hydrate structure may influence different steps of the reaction mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…In reality, water cages-dominated crystalline clathrate hydrates in natural settings and laboratories are imperfect crystals, and inevitably contain defects including water vacancies, interstitial defects and grain boundaries (Roman-Perez et al, 2010;Vidal-Vidal et al, 2015Liang et al, 2016). Similar to other solid crystals, the properties of crystalline clathrate hydrates could be greatly influenced by those defects (Wu et al, 2015;Liang et al, 2016Liang et al, , 2017Lo et al, 2017;Cao et al, 2020Cao et al, , 2021. For example, it was revealed that water vacancy defects in clathrate hydrates promote the local hopping and diffusion behaviors of guest molecules across clathrate cages (Liang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…41−43 The main controlling factors for cage formation are the water− guest and water−water interactions. Moreover, the transient translational and rotational water defects in the crystalline structure can enhance the mass transfer of guest molecules 44,45 (Figure 5), while significant structural defects are presented during hydrate nucleation. 46 These microscopic insights further illustrate that hydrate nucleation is a stochastic process.…”
Section: Ngh Phase Equilibria and Kinetics Research In Chinamentioning
confidence: 99%